Ankle-brachial index and eicosapentaenoic acid/arachidonic acid ratio in smokers with type 2 diabetes mellitus. Issue 1 (December 2016) - Okada, Kenta; Kotani, Kazuhiko; Ishibashi, Shun
Abstract Background The ankle-brachial index (ABI) is an indicator of peripheral arterial damage and a low (ABI ≤ 1.0) or borderline (ABI = 1.00–1.09) value is associated with risk of cardiovascular disease events. A low ratio of serum eicosapentaenoic acid to arachidonic acid (EPA/AA) is also a risk factor for cardiovascular disease events. This study examined associations between the ABI and the EPA/AA ratio in smokers and non-smokers with type 2 diabetes mellitus (T2DM). Findings Blood data including EPA, AA, and ABI were measured in smokers and non-smokers with T2DM enrolled at Jichi Medical University (n  = 116, male 86 %, mean age 59 yr). The patients were classified into two groups according to their ABI level: <1.1 (low to borderline) or ≥1.1 (high). The EPA/AA ratio in smoking patients with ABI < 1.1 (n  = 26; EPA/AA = 0.25) was significantly lower than in those with ABI ≥ 1.1 (n  = 32; EPA/AA = 0.34;p  = 0.03), but was not significantly different in non-smoking patients. The EPA/AA ratio was independently, significantly, and positively correlated with the ABI level (β  = 0.41;p  < 0.01) after adjusting for multiple variables only in smoking patients with T2DM. Conclusions The EPA/AA ratio may be associated with subclinical peripheral arterial damage in smokers with T2DM. Further studies are warranted.